A Conceptual Model of Fate and Transport Processes for RDX Deposited to Surface Soils of North American Active Demolition Sites. Issue 6 (1st November 2017) - Lapointe, Marie‐Claude; Martel, Richard; Diaz, Emmanuela
Abstract : The use of hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine (RDX) as an energetic material (EM) in ammunition constituents such as detonators, primers, mines, and rocket boosters and in plastic explosives has led to an international warning on possible soil, surface water, and groundwater contamination on military training sites. In Canada, the demolition sites of range training areas are known to be the second most contaminated sites by EM residues in terms of their concentrations in soil after anti‐tank ranges. This research proposes a conceptual model of the presence of RDX at the field scale at demolition sites according to previous soil and water characterization studies. This model illustrates the origin of RDX contamination, the main RDX transport pathways and processes, and the main threatened receptors. This conceptual model is of importance to visualize and understand RDX's environmental fate and behavior and to ultimately enable the production of a detailed quantitative model that can help to manage those RDX‐contaminated sites. Core Ideas: RDX is mostly found in the form of aggregates of various sizes and shapes. A field‐scale conceptual model of the source zone of RDX at Canadian demolition sites. We illustrate RDX's complex multiphysical phenomenon and its environmental behavior.